Developing the dematerialization and conversion of plastic waste to resource model for supply chain industry / Jenny Ong - Jenny , Ong (2021)
The generation of industrial solid waste in Malaysia is growing rapidly, in terms of volume and its impacts towards the environment. In this research, the focus was on the management of non-hazardous industrial solid waste, with attention on the plastic packaging waste. It is the responsibility of all industrial players to reduce negative environmental impacts due to their production activities and it was suggested that industrial players to work closely to achieve better waste management system. Moreover, both industrial symbiosis and sustainable supply chain management stressed on the importance of collaboration among industrial players to sustainably manage their wastes. However, study on industrial symbiosis and sustainable supply chain management in Malaysia is quite limited. The objectives of this research are to identify challenges faced by the industrial players, to develop system dynamic models that describe the material flow of plastic packaging wastes and to analyse the outcome of the system dynamic models. A survey was carried out in Rawang Integrated Industrial Park to study the disposal of industrial solid waste practices and to identify challenges faced that could be used as the basis in developing eco-industrial park in the future. Rawang Integrated Industrial Park was selected as it comprised of all sizes of industries, from small and medium industries to large multi-national companies. The questionnaires were distributed using email and followed by telephone calls. Literature review and targeted interview with key players in plastic supply chain were conducted to enable the mapping of interactions between the major industrial players. Subsequently, modelling software named Vensim Ple 7.2 was used to build and analyse the system dynamic models. One of the findings was the food grade plastic industries adopted the open loop supply chain while the non-food grade plastic industries adopted the closed loop supply chain. Therefore, system dynamic models were developed based on forward supply chain, open and closed loop recycling. Results from the model analysis was the projected tonnage of plastic waste in landfill for forward supply chain was 61% higher as compared to open and closed loop supply chain and there was no significance difference between open and closed loop supply chain. Six challenges faced by the industrial players to manage industrial wastes were identified. First, the tonnage of recyclables generated was insufficient to cover the recycler’s collection cost. Second, recycling was not a major concern for majority of the companies in this industrial park as only 34% of the companies have designated personnel responsible for their waste management plan. Third, absence of synergies between the companies in the industrial park because all companies managed their waste independently. Fourth, lack awareness on environmental related policies, where none of the manufacturers were aware that they were required to segregate their wastes. Fifth, the plastic recycling technologies were outdated and sixth, insufficient of recycling facilities. Therefore, to increase recycling rate, it was strongly recommended to have strong collaboration between regulatory bodies and industrial players in developing eco-industrial parks and to implement stringent environmental regulations such as extended producer responsibility to ensure industrial’s compliance.